General Trends in Competition Policy and Investment Regulation in Mandatory Defined Contribution Markets in Latin America - Dayoub, Mariam; Lasagabaster, Esperanza (World Bank, Washington, DC, 2012)
Following Chile's pension reform in 1981, a wave of multi-pillar pension reforms took place in Latin America (LAC). Their implementation has revealed new policy challenges. To shed light on these issues, this paper reviews the structure and performance of mandatory DC pillars in LAC. The review highlights three important points. First, it suggests overall positive outcomes from reforms in the LAC countries that implemented multi-pillar pension systems. There is, however, scope for increasing efficiency. Second, management fees have declined but remain relatively high whereas decreases in operational costs have only been partially passed through to consumers reflecting inadequate competition. Limits on transfers and related measures have been ineffective in curtailing management fees but created new barriers to entry. In recent years, a few countries in LAC introduced or are in the process of introducing a combination of new measures that focus more directly on the two root causes of inadequate competition - the inelasticity of demand to fees and selective elimination of barriers to entry by facilitating unbundling of services. These new measures show some promise. Third, the paper's review indicates that a greater diversification of pension fund portfolios in LAC appears to be necessary. Portfolio concentration owes to the adoption of strict quantitative investment regulations, underdeveloped capital markets and volatile macroeconomic environments. A gradual relaxation of these restrictions is now in progress in several countries. Regulators have become more conscious of the costs imposed by such regulations and macroeconomic conditions have improved. Greater overseas diversification seems inevitable given the development stage of local capital markets.